Lexical and Terminological Study of Synonym: Contexts from the Quran, Sunnah and Arabic Literary Heritage - Usman Abbas; Prof.Dr. Hafiz Muhammad Shahbaz (jihat-ul-islam, 2024)
The Arabic language is superior to all the languages of the world in that it has so many words for one thing. More than one word or name of a thing is called a synonym. The literal meaning of the synonym is one who comes behind, submissive and one who sits back on a ride. Terminology means words that have the same or similar meaning to a single word. Some lexicographers have denied synonyms. In which the name of Abu Hilal Askari is prominent. His famous book is Al-Farooq Al-Lughaviyyah. But the fact is that denial of synonyms is not possible. Because there are many hundreds of names or words for some things in the Arabic language. There are six types of synonyms, understanding of which reveals the reality of synonyms and the difference will end. There are many examples of synonyms in the Holy Quran, Prophetic Hadith and Arabic poetry. This article analyzes the literal and terminological definition of synonyms, its reality, its examples and other important topics.